Pengaruh Kualitas Produk Terhadap Kepuasan Pelanggan pada Produk Bakso Giling Mas Agus di Padang Pariaman - Nurofik, Agus; Indrayani, Tri Irfa; Nini (Jurnal Pustaka Manajemen (Pusat Akses Kajian Manajemen), 2025)
In this study to understand and evaluate the extent to which the influence of product quality on customer satisfaction. Based on the results of the study through a simple Resresi Analysis test, it can be seen that product quality has a significant value of 0.001 <0.05, then Ho is rejected and Ha is accepted. Calculations through the t test state that there is an influence on consumer satisfaction on the Mas Agus minced meatball product in Padang Pariaman. It is recommended to continue to maintain the quality of the Mas Agus minced meatball product in Padang Pariaman which is already good, by continuing to prioritize product quality to achieve maximum customer satisfaction as expected.